2013
DOI: 10.1182/blood-2011-12-397067
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 mediates hematopoietic suppression in MDS by activating TGF-β signaling

Abstract: Key Points We observed that SMAD7, a negative regulator of TGF-β receptor-I kinase, is markedly reduced in MDS, and leads to ineffective hematopoiesis. Increased levels of microRNA-21 are seen in MDS and reduce SMAD7 levels, thus overactivating TGF-β signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 33 publications
5
84
0
1
Order By: Relevance
“…35 However, Bhagat et al recently reported that increased activity of the TGFB pathway is common in MDS patients and that loss of inhibitory function of SMAD-7 is responsible for the dysplastic phenotype. 22,23 In addition to these pathophysiological mechanisms exerted by TGFB we describe MDS patients with increased TGFB and miR-23a levels and decreased CXCL12 levels, which is in accordance with the regulatory effect of TGFB on CXCL-12 via miR-23 described here. Although there is currently no clear experimental evidence of how reduced CXCL12 levels could contribute to MDS, there are some data suggesting that loss of CXCL12/CXCR4 signaling could lead to increased HSPC proliferation, 4,24 which may be a precaution for MDS development.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 88%
See 1 more Smart Citation
“…35 However, Bhagat et al recently reported that increased activity of the TGFB pathway is common in MDS patients and that loss of inhibitory function of SMAD-7 is responsible for the dysplastic phenotype. 22,23 In addition to these pathophysiological mechanisms exerted by TGFB we describe MDS patients with increased TGFB and miR-23a levels and decreased CXCL12 levels, which is in accordance with the regulatory effect of TGFB on CXCL-12 via miR-23 described here. Although there is currently no clear experimental evidence of how reduced CXCL12 levels could contribute to MDS, there are some data suggesting that loss of CXCL12/CXCR4 signaling could lead to increased HSPC proliferation, 4,24 which may be a precaution for MDS development.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 88%
“…patients 22,23 we additionally determined TGFB1 values in a subgroup of samples. We observed a substantial increase in the expression of TGFB1 in MDS samples ( Figure 6C).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Our results are consistent with and expand the impact of prior reports that showed systemic treatment with monoclonal antibodies that target TGFβ ligands or the type II TGFβ receptor inhibit metastatic invasion of breast cancer cells in the 4T1 model [38][39], and previous reports on the impact of systemic treatment with small molecule inhibitors of TGFβ on in vivo xenograft and murine models of metastatic pancreatic cancer and glioblastoma [16][17][18]40]. In addition, our data further support prior reports showing the activity of the TGFβ pathway in promoting MDS [41]. Based on this information, a predefined PK/PD model guided the first-in-human dose escalation study and was critical for defining a predictive and safe therapeutic window [34].…”
Section: Discussionsupporting
confidence: 90%
“…FcgRIIA transgenic mice were treated with 25 mg/kg anti-miR-148a or scrambled anti-miR control for 5 times total on alternative days. We based our treatment on the protocol of Bhagat et al, 31 who used this approach in modulating mouse hematopoietic cell miRNA. The sequence of the chosen 14-nucleotide anti-miR is complementary to mmu/hsa-miR-148a-3p sequence ( Figure 4A).…”
Section: Downregulation Of Mir-148a Led To De-repression Of Tula-2 Inmentioning
confidence: 99%
“…25 In cardiovascular diseases, miRNA inhibition has been used to regulate atherosclerosis, cardiac function, and vascular biology in animal models. [26][27][28][29][30] Bhagat et al 31 showed that anti-miR-21 treatment in mice elevated SMAD7 expression and stimulated hematopoiesis. Garchow et al 32 identified anti-miR-21 effects in a mouse model of systemic lupus erythematosus.…”
Section: Introductionmentioning
confidence: 99%